Pengaruh Latihan Lari Sprint 50m terhadap Peningkatan Speed dan Power Tendangan Dollyo Chagi pada Atlet Taekwondo - Tamara Tsania; Dwikora Novembri Utomo; Abdurrachman Abdurrachman; Damayanti Tinduh (Majalah Kedokteran Indonesia, 2022)
Introduction: Several training techniques are used to improve the performance of taekwondo athletes, one of which is sprint running. Sprinting is one of the branches of athletic sports which requires strength, muscle power, agility and speed. Dollyo chagi kicks is most often used both in attack and defense in taekwondo competition. To be a profesional athlete, they must have sport components such as muscle strengh, muscle power, speed, flexibility, agility, and endurance. The winner of the taekwondo competition is determined by the number of points earned. The author choose the speed an power of dollyo chagi because it is reliable to get points taekwondo matches.Methods: This is a quasi-experimental study with one-group pre-test and post-test design. Using purposive sampling techniques, seventeen junior taekwondo athletes (9 males and 8 female) were recruited. The athletes were trained with 50-meter sprint run for 4 weeks with intensity of 3 sets and 4 times a week. Result: Speed of dollyo chagi kicks increase significantly 17.74% (p less than 0.05) and power of dollyo chagi kicks increase significantly 23.06% (p less than 0.05). Conclusion: 50m sprint training can increase the speed and power of dollyo chagi kicks in taekwondo athletes.